Validation, optimal threshold determination, and clinical utility of the infant risk of overweight checklist for early prevention of child overweight - Redsell, Sarah A.; Weng, Stephen; Swift, Judy A.; Nathan, Dilip; Glazebrook, Cris (2016)
Background: Previous research has demonstrated the predictive validity of the Infant Risk of Overweight Checklist (IROC). This study further establishes the predictive accuracy of the IROC using data from the Avon Longitudinal Study of Parents and Children (ALSPAC) and examines the optimal threshold for determining high risk of childhood overweight.